Mixed legume systems of pea protein and unrefined lentil fraction: Textural properties and microstructure. (June 2021) - Johansson, Mathias; Xanthakis, Epameinondas; Langton, Maud; Menzel, Carolin; Vilaplana, Francisco; Johansson, Daniel P.; Lopez-Sanchez, Patricia
Abstract: Within the context of circular economy, there is an increasing interest to utilise agrifood by-products. However, extensive extraction and purification steps make the valorisation of side streams not always cost effective. Therefore, an increased knowledge of the functionality of unrefined side streams could increase their utilisation in food products. We investigated the thermal gelation of mixed legume systems containing a commercial pea protein isolate ( Pisum sativum ) and the unrefined fraction remaining after protein extraction from lentils ( Lens culinaris ). The unrefined lentil fraction contained mainly starch ( 45 g/100 g) and insoluble cell wall polysaccharides ( 50 g/100 g) with minor amounts of soluble protein (4 g/100 g) and polyphenols (<1 mg GAE/g). The addition of the unrefined lentil fraction increased the strength and Young's modulus of pea protein gels in the pH range 3–4.2, and also increased the gels' elastic modulus G'. The microstructure could be described as a mixed network of swollen protein particles of different sizes (5–50 μm), gelatinised starch and cell wall fragments. The results demonstrate that unrefined side streams from lentils could be used for textural modification of plant protein gels, with implications for the design of novel plant-based foods. Highlights: A lentil side-stream contained mainly starch and cell wall polysaccharides. Addition of the unrefined fraction increased the strength of pea protein gels. Starch increased the strength and elasticity of the pea protein gels. Unrefined side streams could be used to modify texture of pea protein gels.